Through The Shattering Glass : Cervantes and the Self-Made World - Spadaccini, Nicholas (Book collections on Project MUSE., 1992)
"By considering the dialectical nature of Cervantes' work as a whole, Spadaccini and Talens broaden our understanding of the uniqueness of his art. . . . Through the Shattering Glass is a welcome and highly significant contribution to Cervantine scholarship." Hispania. "Offers an important new approach to Cervantes's works, which have been studied in toto by relatively few critics.".